The analysis of postural control ability in athletes with rotational motion - Iwata, H.; Nakata, H.; Kobayashi, K.; Uchida, Y.; Momose, K.; Kanosue, K. (Sport Science Research, 2011)
Figure skate, ballet dance and contest dance are sports including rotational motion. Athletes in these sports are required postural control in order to perform under the rotational stimulation. The better they adapt to the rotational stimulation, the better they can perform, particularly, right after a rotational movement. The purpose of this study is to investigate how athletes can adapt to rotational stimulation. Subjects sit in a computerized rotary chair and experience repeated rotations for forty seconds. During the rotation the subjects opened their eyes with or without an adaptational skill called "spotting", or closed their eyes. Immediately after the stimulation, they maintain upright posture with their eyes opened. The head movement and smooth-persuit component of eye movement after the end of rotation are smaller in the expert group than in the control group both with eyes open and closed. In addition, when the "spotting" skill was used, the head and eye movements became even smaller. A dancer gazes at one point till when it becomes impossible, and then quickly rotates the head back so that the same point could be seen again. It seems that dancers are adapted to rotation not only physiologically but also with special skill.